ANALISIS DAN OPTIMALISASI KUALITAS JARINGAN DENGAN MENGGUNAKAN PARAMETER QUALITY OF SERVICE (QOS) DI REKTORAT UNIVERSITAS TEKNOLOGI SUMBAWA - Yunan Wijaya; Yuyun Safitri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Analyzing the performance of the network at the Rectorate of Universitas Teknologi Sumbawa based on Quality of Service parameters, namely throughput, jitter, delay, and packet loss; identifying the causes of the degradation in network quality; and formulating recommendations for technical improvements and optimization so that the network at the Rectorate of Universitas Teknologi Sumbawa can operate more stably and efficiently.The research methods used are interviews and literature study. The researcher conducted an analysis of network quality at several traffic periods, namely morning, afternoon, and evening. The results obtained based on the TIPHON standard show that in the first test, throughput is categorized as poor according to the TIPHON standard, while packet loss is categorized as very good, delay is categorized as very good, and jitter is also categorized as very good. The measurement results after optimization, adjusted to the TIPHON standard, indicate that throughput is categorized as very good, delay is categorized as very good, and packet loss is also categorized as very good.Factors affecting network quality include the number of active users, bandwidth capacity, traffic management, and network device configuration. This study recommends increasing bandwidth capacity, implementing QoS-based traffic management on network devices, conducting periodic monitoring, and evaluating infrastructure to ensure more optimal internet service quality, especially in supporting technology-based public services. Keyword: Analysis,Optimization,Wireless Local Area Network, Quality of Service, Wireshark   Abstrak:Menganalisis Kinerja jaringan di Rektorat Universitas Teknologi Sumbawa berdasarka parameter quality of service throughput, jitter, delay, dan paccket loss,Mengidentifikasi penyebab penurunan kualitas jaringan ,Menyusun Rekomendasi perbaikan dan optimalisasi kualitas jaringan  teknis agar jaringan di rektorat Universitas Teknologi Sumbawa dapat beroprasi dengan lebih stabil dan lebih efisien. Metode penelitian yang di guanakan yaitu ,wawancara dan study pustka peneliti melakukan analisis kualitas jaringan dengan beberapa trafik waktu tertentu yaitu pagi,siang dan sore.kemudian hasil yang di perolah berdasarkan standar TIPHON pada pengujian pertama yaitu throughputh di katakan buruk menurut stadar TIPHON,paket loss di katakan sangat baik ,delay di katakan sangat baik dan jitter di katakan sangat baik pula berdasarkan standar TIPHON. Hasil pengukuran setelah optimalisasi di sesuaikan dengan standar TPHON yaitu throughput di katakan sangat baik,delay di katakan sangat baik dan packet loss di katakan sangat baik pula.. Faktor yang memengaruhi kualitas jaringan meliputi jumlah pengguna aktif, kapasitas bandwidth, manajemen trafik, dan konfigurasi perangkat jaringan.Penelitian ini merekomendasikan peningkatan kapasitas bandwidth, penerapan manajemen trafik berbasis QoS pada perangkat jaringan, monitoring berkala, dan evaluasi infrastruktur untuk memastikan kualitas layanan internet yang lebih optimal, khususnya dalam mendukung pelayanan publik berbasis teknologi. Kata Kunci : Analisis, Optimalisasi, jaringan, Qos, Wireshark